Professor Kenneth John Gregory (1938–2020): The career, contributions and legacy of an eminent geographer and fluvial geomorphologist. Issue 1 (24th April 2022) - Gurnell, Angela; Downs, Peter; Tooth, Stephen; Wharton, Geraldene
Abstract: This paper provides the editorial to accompany a Special Issue of Earth Surface Processes and Landforms produced to honour the memory of Professor Ken Gregory, a key figure in late 20th‐ and early 21st‐century geography and geomorphology. It provides an overview of Ken Gregory's career in research, teaching, and university administration, and elaborates on his key research contributions and legacy across geography and geomorphology. Ten interrelated research themes are identified where Ken made particular impacts: (1) river catchment processes and process–form relationships; (2) wood in rivers; (3) anthropogenic impacts on rivers and catchments; (4) approaches to river management that better respect natural processes; (5) public perceptions of rivers; (6) quantitative palaeohydrology; (7) chronology of river floods and deposits; (8) key physical geography/geomorphology concepts and their metrics; (9) the nature of the discipline of physical geography; and (10) concepts in physical geography teaching. These themes provide a framework to introduce the papers in this Special Issue. Through his publications, leadership style, personality, and positive influence on the many people with whom he interacted, Ken Gregory has left a legacy that will continue to inspire present and future generations of geographers and geomorphologists. Abstract : This paper provides the introduction to a Special Issue of Earth Surface Processes and Landforms produced to honour the memory of Professor Kenneth John Gregory, a key figure in late 20th‐ and early 21st‐century geography and geomorphology. It provides an overview of Ken Gregory's career in research, teaching and university administration, and elaborates on his key research contributions and legacy across geography and geomorphology.